Analysis on the Determinants of Republic of Indonesia Sovereign Sukuk Liquidity in Secondary Market - Pranata, Bahal Anugrah; Rokhim, Rofikoh (Devotion : Journal of Research and Community Service, 2024)
This study investigates the determinants of liquidity in Sharia Securities (SBSN) by analyzing the impact of bond-specific and macroeconomic factors on the bid-ask spread as a proxy for liquidity. Using panel data regression analysis, the study examines 62 tradable series of SBSN from 2013 to 2022, considering factors such as outstanding amount, time to maturity, yield to maturity, Rupiah exchange rate, inflation rate, reference interest rate, Indonesia Stock Exchange Composite Index (IHSG), and Indonesia Credit Default Swap (CDS). Results indicate that time to maturity, yield to maturity, central bank reference interest rate (BIRate), IHSG, and CDS significantly influence the bid-ask spread of SBSN, while outstanding amount, Rupiah exchange rate, and inflation rate do not. Additionally, analysis reveals that a strengthening IHSG and higher CDS widen the bid-ask spread, indicating reduced liquidity. These findings provide insights for stakeholders including issuers, investors, and regulators in managing SBSN liquidity in the Indonesian market.